2002
DOI: 10.1111/j.1574-695x.2002.tb00611.x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed lethal response toAspergillus fumigatusinfection in sarcoma 180 tumor-bearing mice

Abstract: A longer survival and a decrease in the number of fungal cells in kidneys and brain were observed in groups of mice inoculated with Aspergillus fumigatus conidia 2-3 weeks (especially 3 weeks) after sarcoma 180 tumor transplantation compared to groups of non-tumor-bearing (control) mice inoculated with fungal cells only. The 3-4-week tumor-bearing mice had significantly decreased levels of serum iron and increased levels of unbound iron binding capacity in the serum compared to those of the non-tumor-bearing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…[2][3][4][5][6] The protective activity of allogeneic sarcoma 180 tumor-bearing mice against Candida albicans and Aspergillus fumigatus infections has been reported in our previous papers. [7][8][9][10][11] It has also been reported that there is a significant delay in the lethal response to C. albicans in mice bearing Lewis lung carcinoma. 12) However, the mechanisms of such an effect have yet to be fully elucidated.…”
mentioning
confidence: 99%
“…[2][3][4][5][6] The protective activity of allogeneic sarcoma 180 tumor-bearing mice against Candida albicans and Aspergillus fumigatus infections has been reported in our previous papers. [7][8][9][10][11] It has also been reported that there is a significant delay in the lethal response to C. albicans in mice bearing Lewis lung carcinoma. 12) However, the mechanisms of such an effect have yet to be fully elucidated.…”
mentioning
confidence: 99%
“…Alternative procedures were developed to allow invasive aspergillosis in very original opportunistic contexts, like septic infections following caecal ligation and puncture (Benjamim et al, 2003, 2005), as well as cancerous disease using 1.0 × 10 6 S-180 tumor cells suspension (Okawa et al, 2002), and rhinosinusitis after unilateral nasal obstruction with sponges (Zhang et al, 2013). In addition to all these abovementioned methods, rodents were sometimes fed with low-diet hypo-protein regimen to mimic the malnourished status of the weakest human patients that are usually infected with A. fumigatus in hospitals (Miyazaki et al, 1993; Mitsutake et al, 1995; Chandenier et al, 2009; Lo Giudice et al, 2010; Desoubeaux and Chandenier, 2012; Desoubeaux et al, 2014b).…”
Section: Resultsmentioning
confidence: 99%